2006
DOI: 10.1038/labinvest.3700412
|View full text |Cite
|
Sign up to set email alerts
|

Functional facets of the pulmonary neuroendocrine system

Abstract: Pulmonary neuroendocrine cells (PNECs) have been around for 60 years in the scientific literature, although phylogenetically they are ancient. Their traditionally ascribed functions include chemoreception and regulation of lung maturation and growth. There is recent evidence that neuroendocrine (NE) differentiation in the lung is regulated by genes and pathways that are conserved in the development of the nervous system from Drosophila to humans (such as achaete-scute homolog-1), or implicated in the carcinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
146
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 188 publications
6
146
3
Order By: Relevance
“…The reduced proliferation and apoptosis of Gfi1 À/À airway epithelium was associated with a profound impairment in the absolute levels of NE marker expression and BrdU þ CGRP þ cells. Although these results might support a previously hypothesized paracrine and growth stimulatory role of PNEC, 7 we found no difference in the post-naphthalene induced rate of proliferation and apoptosis in wt vs Gfi1 À/À terminal airway epithelial cells. Moreover, regeneration of the CC10 þ cells was virtually identical between wt and Gfi1 À/À littermates.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The reduced proliferation and apoptosis of Gfi1 À/À airway epithelium was associated with a profound impairment in the absolute levels of NE marker expression and BrdU þ CGRP þ cells. Although these results might support a previously hypothesized paracrine and growth stimulatory role of PNEC, 7 we found no difference in the post-naphthalene induced rate of proliferation and apoptosis in wt vs Gfi1 À/À terminal airway epithelial cells. Moreover, regeneration of the CC10 þ cells was virtually identical between wt and Gfi1 À/À littermates.…”
Section: Discussioncontrasting
confidence: 52%
“…[2][3][4][5] Pulmonary damage caused by chronic lung diseases, hypoxia, hyperoxia, extended exposure to environmental pollutants such as tobacco smoke, nitrosamines, ozone and naphthalene induces PNEC proliferation. 6,7 Naphthalene is an aromatic hydrocarbon that is a constituent of tobacco smoke. 8 Naphthalene specifically ablates the non-ciliated epithelial Clara cells that are most abundant in the bronchiolar epithelium.…”
mentioning
confidence: 99%
“…13,14 Furthermore, these vCE cells are harbored and maintained within a microenvironment or niche, which is provided by PNECs/NEBs through the paracrine secretion of various neuropeptides and bioactive amines. 48 It has also previously been shown that acute naphthalene toxicity results in PNEC/NEB hyperplasia in mice, 49 and after examination of PNECs/NEBs in our study, we found no observable difference in the extent of PNEC/NEB hyperplasia between Elf3 þ / þ and Elf3À/À mice after naphthalene exposure (data not shown).…”
Section: Discussioncontrasting
confidence: 41%
“…However, we cannot rule out similar regulatory functions for other PNEC-derived neuropeptides. PNECs have been implicated as regulators of ventilationperfusion mismatches in response to hypoxia (16,58). Bronchoconstrictor and vasoconstrictor responses could be homeostatic in normal lung, maintaining optimal ventilation-perfusion matching despite regional hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In lung, only PNECs produce GRP (16). GRP is present at high levels in human and mouse fetal lung (17,18), and GRP regulates normal development (18,19).…”
mentioning
confidence: 99%